Self-assembling peptides for sciatic nerve regeneration: a review of conduit microenvironment modeling strategies in preclinical studies - Stocco, Elena; Barbon, Silvia; Zamuner, Annj; Confalonieri, Marta; Tiengo, Cesare; De Caro, Raffaele; Macchi, Veronica; Dettin, Monica; Porzionato, Andrea (Frontiers in Cell and Developmental Biology, 2025)
Effective nerve conduits development remains a significant challenge in regenerative medicine, with the potential to greatly improve patients’ quality of life in case of peripheral nerve injury. To date, several tubular devices have been introduced into clinical practice; however, the outcomes remain suboptimal. As empty conduits, lacking internal guidance structures or bioactive elements, they provide minimal support for nerve regeneration and fail especially in cases of long-gap nerve injuries. In this scenario, intense research efforts are directed toward improving conduit-associated results in vivo. Among the most promising strategies, the in-situ addition of luminal fillers has shown great potential in creating favorable microenvironment for axonal growth and tissue remodeling. Considering the many luminal fillers explored and reported in the literature, Self-Assembling Peptides (SAPs) have achieved significant attention by the scientific community due to their unique ability to arrange into biocompatible, extracellular matrix-like hydrogels that can favorably support axons and Schwann cells regeneration and organization within the conduit, guiding growth toward the distal stump. This review focuses on the use of SAP-based hydrogels as luminal fillers for sciatic nerve repair, summarizing the most relevant in vivo findings and highlighting their potential to enhance nerve regeneration.